Improved corrosion resistance of Al2O3 ceramic coatings on AZ31 magnesium alloy fabricated through cathode plasma electrolytic deposition combined with surface pore-sealing treatment. Issue 13 (September 2018) - Ji, Ruonan; Ma, Minyu; He, Yuntao; Liu, Chenxu; Fang, Tao; Zhang, Zhan; Wang, Yi; He, Yedong; Wu, Junsheng
Abstract: In this study, we explored the phase compositions and morphologies of the ceramic coatings from different aluminum sources (aluminum isopropoxide, aluminum nitrate, or a mixture of the two) prepared using cathode plasma electrolytic deposition (CPED) onto AZ31 magnesium alloys. Scanning electron microscopy and X-ray diffraction analyses of these coatings indicate that the deposited ceramic made from aluminum isopropoxide was composed of γ-Al2 O3 whereas the one made from aluminum nitrate was composed of MgA12 O4, and that the former was more compact and uniform than the latter. A composite coating was prepared using epoxy resin as a protective layer that sealed the micropores on the CPED coating, thereby further improving its anticorrosion property. The elemental distribution of the cross-section of the composite coating was examined via energy dispersive spectroscopy. Corrosion resistance was investigated using potentiodynamic polarization curves and electrochemical impedance spectroscopy in a 3.5 wt% NaCl medium, and a salt spray test. The results indicate that the corrosion protection property of the Al2 O3 /epoxy resin coating of the magnesium alloy was better than that of the single Al2 O3 coating. A cross-cut test revealed that the adhesion of the Al2 O3 /epoxy resin composite coating to the magnesium alloy surface was better than that of the single epoxy resin coating. The approach presented herein provides an attractive way to modify the surface of magnesium alloys to improve anticorrosion.